The 1994 good weekend guide - Aird, Alisdair (London Vermillon, 1994)
if you are planning a weekend break, combining a business trip with pleasure, getting away from the children or giving them a special trat, The Good Weekend Guide is packes with ideas on where to go, whenever you want to enjoy the best entertainment in Britain.
Keywords: Country Studies